2022
DOI: 10.1186/s12890-022-02232-3
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal swallowing physiology and safety in patients with Idiopathic Pulmonary Fibrosis: a consecutive descriptive case series

Abstract: Introduction Dysphagia occurs in multiple respiratory pathophysiologies, increasing the risk of pulmonary complications secondary to aspiration. Reflux associated aspiration and a dysregulated lung microbiome is implicated in Idiopathic Pulmonary Fibrosis (IPF), but swallowing dysfunction has not been described. We aimed to explore oropharyngeal swallowing in IPF patients, without known swallowing dysfunction. Methods Fourteen consecutive outpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…We have previously provided quantitative data showing that dysregulated swallowing physiology can occur in patients with IPF, which included fluoroscopic evidence of aspiration. 14 Non-sterile aspiration represents a candidate source of complex lung injury and microbiome dysregulation and the present study provides novel complimentary information that provides qualitative data regarding eating and drinking in patients with IPF.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…We have previously provided quantitative data showing that dysregulated swallowing physiology can occur in patients with IPF, which included fluoroscopic evidence of aspiration. 14 Non-sterile aspiration represents a candidate source of complex lung injury and microbiome dysregulation and the present study provides novel complimentary information that provides qualitative data regarding eating and drinking in patients with IPF.…”
Section: Discussionmentioning
confidence: 91%
“…These studies have identified issues with patients obtaining a correct and timely diagnosis; accessing suitable information about their condition; and substantial physical and psychosocial impacts on themselves and carers, affecting their overall Ouality of Life (QOL) 10 13. We have also published preliminary work which noted that around a third of patients with IPF reported difficulties with eating and drinking using a patient-reported measure 14. Further qualitative work is warranted to understand this problem in more depth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation